2011
DOI: 10.1002/dc.21717
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing's sarcoma/primitive neuroectodermal tumor of the kidney: Report of a case diagnosed by fine needle aspiration cytology and confirmed by immunocytochemistry and RT‐PCR along with review of literature

Abstract: Primary Ewing's sarcoma/primitive neuroectodermal tumor (ES/PNET) of the kidney is a distinct entity that can be mistaken for variety of round cell tumors. We report a rare case of ES/PNET of the kidney in a 35-year-old female patient diagnosed by fine needle aspiration cytology (FNAC) and confirmed by immunohistochemistry (IHC) and reverse-transcriptase polymerase chain reaction (RT-PCR). Ultrasound guided FNAC smears from the kidney mass showed a population of malignant small round cells with perivascular ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…WT-1, a common marker for Wilms' tumor, has been used to rule out the diagnosis of PNET, while rPNETs may stain positive for WT-1. A cytogenetic study performed to detect the EWS/FLI-1 fusion gene revealed a translocation of chromosomes 11 and 22, t(11:22) (q24:q12), in >90% of rPNET cases (18), while the use of FISH for the detection of the fusion gene may increase the specificity of this marker and decrease false-positive test results. In the present study, FISH detection was performed for one case, also revealing t(11;22)(q24;q12) translocation.…”
Section: Discussionmentioning
confidence: 99%
“…WT-1, a common marker for Wilms' tumor, has been used to rule out the diagnosis of PNET, while rPNETs may stain positive for WT-1. A cytogenetic study performed to detect the EWS/FLI-1 fusion gene revealed a translocation of chromosomes 11 and 22, t(11:22) (q24:q12), in >90% of rPNET cases (18), while the use of FISH for the detection of the fusion gene may increase the specificity of this marker and decrease false-positive test results. In the present study, FISH detection was performed for one case, also revealing t(11;22)(q24;q12) translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, it can be challenging to differentiate renal ES from other SRBCTs, synovial sarcoma, malignant lymphoma, WT, neuroblastoma and small cell neuroendocrine tumour because these tumours often show overlapping cytomorphological features 13. Therefore, immunocytochemistry and detection of the translocation by FISH or RT-PCR techniques have always been critical in reaching the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The translocation of t(11:22) (q24:q12) with the fusion transcript between the EWS gene (22q12) and the ETS-related oncogene (11q24) have been detected in more than 90% of the rPNET [5]. Several studies applied preoperative fine needle aspiration cytology to diagnose rPNET based on the constellation of cytomorphologic and immunohistochemical findings with subsequent confirmation by cytogenetic analyses [11-13]. …”
Section: Discussionmentioning
confidence: 99%